Structure of liquid Al2O3 from a computer simulation model - Hemmati, M; Wilson, M; Madden, P (1999)
The combination of new containerless sample and high intensity synchrotron source technologies has enabled the X-ray diffraction pattern from a molten oxide (Al2O3) to be determined for the first time (Ansell et al. Phys. Rev. Lett. 1997, 78, 464).1 Here we show that the liquid-state diffraction pattern, predicted from a computer simulation with a potential derived from the ground-state crystal structure, agrees very well with the experimental data. Analysis of the local structure in the simulated melt shows that the A13+ ions are not predominantly tetrahedrally coordinated, as surmised in the experimental study. Rather, six-, five- and four-coordinate A13+ ions are found. Furthermore, evidence is presented for a tendency of the different coordinate species to spatially separate, and it is suggested that Al2O3 is close to a liquid-liquid phase separation of the type recently discussed by Angell and co-workers (ACS Symp. Ser. 1997, 676, 214).2 © 1999 American Chemical Society.